On Boxing Critical Interventions in the Bittersweet Science - Lewandowski, Joseph D (Taylor & Francis, 2022)
aesthetics; boxer; boxing; constraint; cool; cornerman; culture; ethics; ethnography; gym; identity; martial arts; philosophy of sport; pugilism; social capital; status; sweet science; urban; violence